Perubahan Mata Pencaharian dan Proses Adaptasi Warga Terkena Dampak Pembangunan Waduk Jatigede - Valentina Wijayanto; Opan Suwartapradja; Rina Hermawati (Universitas Padjadjaran, 2017)
The construction of Jatigede dam has brought social, economic, and cultural impact towards the daily living of the surrounding community. One of the socio-economic impacts is the loss of livelihood. As the consequence the community members need to change their form of livelihood and adjust it to the characteristics of the new environment where they live. This study describes the livelihood change and adaptation of community members impacted by the construction of Jatigede dam. It aims at describing the change at the level of infrastructure and structure of the culture in regards with livelihood change of the community using theory of cultural materialism by Marvin Harris as the perspective. This study was conducted using qualitative methods. The result of the study suggests that the changing geographical landscape has brought change to livelihood change from agricultural farming to non-agricultural. In line with this change, community members use their social relations, intra or intergroup, in order to utilize and to adjust to the available resources in the new environment as well as to adjust to it.